2015
DOI: 10.1002/2015gc005716
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and geochemical characterization of Andosols developed on basalts in the Massif Central, France

Abstract: Identification of Andosols is primarily based upon the content of their colloidal constituentsclay and metal-humus complexes-and on the determining of andic properties. This needs time and costconsuming geochemical analyses. Our primary aim of this study is to describe the magnetic and geochemical properties of soils rich in iron oxides derived from strongly magnetic volcanic basement (in this case Andosols). Secondary aim is to explore links between magnetic and chemical parameters of andic soils with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In turn, magnetic susceptibility was increasing down slope ( Figure 3a). Recent studies on volcanic soils showed that magnetic susceptibility is positively correlated to andic properties (Grison et al, 2015(Grison et al, , 2016Vingiani et al, 2014). In xeric conditions, as in the eastern part of the study area, non-crystalline minerals formation is restricted (McDaniel et al, 2012), and thus, andic properties and magnetic enhancement are not strong.…”
Section: Soil Magnetic Susceptibilitymentioning
confidence: 95%
“…In turn, magnetic susceptibility was increasing down slope ( Figure 3a). Recent studies on volcanic soils showed that magnetic susceptibility is positively correlated to andic properties (Grison et al, 2015(Grison et al, , 2016Vingiani et al, 2014). In xeric conditions, as in the eastern part of the study area, non-crystalline minerals formation is restricted (McDaniel et al, 2012), and thus, andic properties and magnetic enhancement are not strong.…”
Section: Soil Magnetic Susceptibilitymentioning
confidence: 95%
“…In relation to this, MS correlates negatively with Fe in section 4 (r 2 = 0.90, again excluding sample 4028), and positively with the proportion of sand (r 2 = 0.58). If these results are considered together with the higher Fe content in finer fractions, it is deduced that (1) section 4 is generally more weathered than the sand-rich deposits from section 11; (2) the majority of Fe released upon weathering is forming secondary oxides with low magnetism (see Grison et al, 2015), such as goethite or hematite; and (3) the high MS in deposit 4026 in section 4 would be attributable to inherited fresh material, most likely magnetite, which is a ferrimagnetic mineral, and previous studies have demonstrated that magnetite is usually more abundant in the sand fractions (Viana et al, 2006).…”
Section: Psa and Msmentioning
confidence: 99%
“…According to Soil Survey Staff (2010), the Andosols cover approximately 0.8 % of the Earth's surface, and approximately 60 % of volcanic ash soils occur in tropical countries such as Colombia (Espinosa and Sanabria, 2015), Central México (Sedov et al, 2003), India (Caner et al, 2000), New Zealand (Neall, 1977). The remaining 40 % occur in cooler climate regions and are derived from various types of volcanic rocks, such as andesite, dacite, volcanic ash, basalt, and ignimbrite, distributed in different countries: Chile (Bertrand et al, 2008), Argentina (Candan and Broquen, 2009), Italy (Vingiani et al, 2014(Vingiani et al, , 2018, France (Grison et al, 2015), Germany (Rennert et al, 2014), Georgia (Urushadze et al, 2011), Turkey (Kiliç et al, 2018), Kamchatka Peninsula of Russia (Litvinenko and Zakharikhina, 2009); and on non-volcanic rocks as gabbros, amphibolites, basic granulites, biotitic schists, amphibolitic phyllites: Spain (Bech-Borras et al, 1977;Garcia-Rodeja et al, 1987).…”
Section: Introductionmentioning
confidence: 99%